Lessons from a review of physiotherapy and psychological rehabilitation received during ICU stay and beyond to inform the development of an ICU follow clinic. (May 2022) - Clarke, Rachel; Schofield, Holly; Tantam, Kate
Background: Critical illness can have a long-term impact. A service evaluation was conducted in a hospital in the south west of Britain with an adult inter-connected general, surgical and neurological intensive care unit (ICU). The aim of the service evaluation was to generate knowledge on experiences of psychological and physical rehabilitation in intensive care, on other hospital wards and at home to inform the development of an Intensive Care follow up clinic. Method: Data was collected from two sources. A week of ICU discharges was randomly selected, and a sample of 30 patients generated. All were sent information sheets and consent forms and offered telephone appointments. 12 participants took part in telephone interviews. The second source of participants was the ICU Expert by Experience group. Informed consent was gained with eight participants taking part. The data was analysed using thematic analysis, employing initial open coding to build a framework of emergent themes. A research group was formed to facilitate cross coding of extracts. Results: The analysis identified three overarching themes: sense making difficulties; rehabilitation context; and sense of self. The theme of sense making difficulties had sub-themes of memory gaps, delirium, lack of information and anxiety. The theme of rehabilitation context had sub-themes of ICU environment, transitions, isolation and abandonment and valued support. Conclusion: the process of sense making can be difficult, is filtered through contextual factors, and may influence sense of self. The results have been used to inform the development of an ICU follow up clinic.